The influence of Good Corporate Governance on the financial performance of State-Owned Enterprises listed on the Indonesia Stock Exchange - Alie, Maria Septijantini; Fitri, Egi Rodlia; Desmon, Desmon; Nasir, M.; Meidasari, Evi (Goodwood Publishing, 2024)
Purpose: This study aims to determine the effect of Good Corporate Governance on the Financial Performance of BUMN Companies listed on the Indonesia Stock Exchange in 2019-2023. Methodology: This study used a quantitative approach. This study used 70 research samples. This study has two variables, namely: 4 independent variables (X1, X2, X3, and X4) and 1 (one) dependent variable. Institutional leadership (X1), board of directors (X2), board of commissioners (X3), and audit committee (X4) are independent variables, while financial performance (Y) is the dependent variable. Results: Based on data analysis, it has been found that the answer to the hypothesis is that institutional ownership, board of directors, board of commissioners, and audit committee simultaneously and partially have a significant effect on financial performance in BUMN companies listed on the Indonesia Stock Exchange in 2019-2023. Conclusion: Good corporate governance (CG) (institutional ownership, board of directors, board of commissioners, and audit committee) significantly affects the financial performance of state-owned enterprises on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The effective implementation of GCG can increase ROA and company value. Limitations: The independent variables in this study are limited to institutional ownership, board of directors, and audits. First,ee, and the dependent variable is financial performance (ROA). The research was conducted only on BUMN companies listed on the Indonesia Stock Exchange. Contribution: Management is expected to pay more attention to Good Corporate Governance in the company in order to create good company value.